Fat Wasting Is Damaging: Role of Adipose Tissue in Cancer-Associated Cachexia - Sun, Xiaoting; Feng, Xiaogang; Wu, Xiaojing; Lu, Yongtian; Chen, Kaihong; Ye, Ying (Frontiers in Cell and Developmental Biology, 2020)
Loss of body weight, especially loss of adipose tissue and skeletal muscle weight, characterize cancer-associated cachexia (CAC). Clinically, therapeutic options for CAC are limited due to the heterogeneity of signaling between cancer and other organs. Recent research advances show that adipose tissues play a critical role during thermogenesis, glucose homeostasis, insulin sensitivity, and lipid metabolism. Understanding the adipocyte lipolysis, the formation of beige adipocyte, and the activation of brown adipocyte is vital for novel therapies for metabolic syndromes like CAC. The systemic-level crosstalk between adipose tissue and other organs involves browning, lipolysis, and secreted factors. Novel CAC animal models and accumulating molecular signaling knowledge have provided mechanisms that may ultimately be translated into potential therapeutic possibilities that benefit CAC patients. This mini-review discusses the role of adipose tissue in CAC development, mechanism and therapy.